Staphylococcal Scalded Skin Syndrome in an Infant - Taksande, A; Vilhekar, K (Journal of Nepal Paediatric Society, 2012)
Staphylococcal scalded skin syndrome is a bullous disease of the skin caused by toxins (exfoliatins) secreted by certain types of Staphylococcus aureus. These toxins may act as superantigens, stimulating the proliferation of T lymphocytes, with a massive release of cytokines and consequent epidermal damage. In neonates, the lesions are mostly found on the perineum or periumbilically, while the extremities are more commonly affected in older children. The disease begins with erythema and fever, followed by formation of large fluid filled bullae which quickly rupture on slightest pressure to leave extensive areas of denuded skin. We present a case of staphylococcal scalded skin syndrome in infant. J Nepal Paediatr Soc 2012;32(2):178-180 doi: http://dx.doi.org/10.3126/jnps.v32i2.5494